Inappropriate use of arthroscopic meniscal surgery in degenerative knee disease: An observational study from Switzerland. (3rd September 2017) - Muheim, Leander L S; Senn, Oliver; Früh, Mathias; Reich, Oliver; Rosemann, Thomas; Neuner-Jehle, Stefan M
Abstract : Background and purpose — Current evidence suggests that arthroscopic knee surgery has no added benefit compared with non-surgical management in degenerative meniscal disease. Yet in many countries, arthroscopic partial meniscectomy (APM) remains among the most frequently performed surgeries. This study quantifies and characterizes the dynamics of the current use of knee arthroscopies in Switzerland in a distinctively non-traumatic patient group. Methods — We assessed a non-accident insurance plan of a major Swiss health insurance company for surgery rates of APM, arthroscopic debridement and lavage in patients over the age of 40, comparing the years 2012 and 2015. Claims were analyzed for prevalence of osteoarthritis, related interventions and the association of surgery with insurance status. Results — 648, 708 and 647, 808 people were examined in 2012 and 2015, respectively. The incidence of APM, debridement, and lavage was 388 per 10 5 person-years in 2012 and 352 per 10 5 person-years in 2015 in non-traumatic patients over the age of 40, consisting mostly of APM (96%). Between years, APM surgery rates changed in patients over the age of 65 (p < 0.001) but was similar in patients aged 40–64. Overall prevalence of osteoarthritis was 25%. Insurance status was independently associated with arthroscopic knee surgery. Interpretation — APM is widely used in non-traumatic patients in Switzerland, which contrasts with current evidence. Many procedures take place in patients with degenerative knee disease. Surgery rates were similar in non-traumatic middle-aged patients between 2012 and 2015. Accordingly, the potential of inappropriate use of APM in non-traumatic patients in Switzerland is high.